Новелістика Ірини Вільде крізь призму гендерології - Карабльова, Ольга; Karableva, Olga (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті за допомогою гендерної методології досліджено сюжетні моделі двох новел Ірини Вільде. Схарактеризовано принцип контраверсійного групування сюжетного матеріалу. Підтверджено, що провідним у конфліктології новел є гендерний родовий конфлікт; установлено, що зміна гендерних ролей є основою подієвості у творах. In contemporary literary forms genderological direction the object of which are fixed in literature the social-psychological stereotypes of femininity and maskulinity, which requires a certain correction. Plot model of two short stories by Irina Wilde investigated with gender methodology. Main vital contradictions in the story of art revealed through the conflict. Writer, dividing world view of Olga Kobylyanska and Lesia Ukrainka, well understood features of gender conflict and its great potential converts. Principle of the contradictory grouping of a plot material, many-sided nature of conflict, gender imbalance is characterized in a short story «Roman gets married». It is set that gender aspect of conflict of short story «Comrade Manya» related to changing of gender roles, which is basis of action in work. It is well-proven that a gender family conflict comes forward dominant of both short stories, although essence of its display is different. Using a gender perspective in the study of prose by Irina Wilde, is expected to expand the boundaries of literary research.
Novels of Irina Vilde Through the Prism of Genderology
Keywords: гендерна методологія; сюжетна модель; контраверсійність; гендерний конфлікт; гендерна роль; гендерний дисбаланс; gender methodology; plot model; contradiction; gender conflict; gender role; gender imbalance